L’invitation comme co-construction et émergence d’un événement - Veyrier, Clair-Antoine (Neophilologica, 2014)
This article aims at analyzing the endogenous co-construction of gathering as an event by examining interactional sequences prior to occurring of this event. Meeting is a form of exchange, and also an interactional event recognized as such by the participants. In this perspective, the invitation is not only a form of coordination, but it participates to the co-construction of the meeting as an event. The study is based on a conversation analysis inspired by ethnomethodology. The analysis uses a collection of invitations to meeting (planned or ad hoc, face-to-face or distant), extracted from a larger corpus. By a detailed analysis of sequences of exchanges, I show the in situ production of an ordinary event, a “meeting”. The activity of inviting shapes an activity as taking place in the future. It produces an accountable and autonomous object of discourse. What is at stake is not so much planning what will be said and how, but the co-construction of the exchange as an event. Invitation is a situated action which aims at producing resources (instructed actions) for a local or future coordination. The event is co-constructed by the exchanges and stabilized by the production of an invitation-announcement.